New Pliocene remains of Camelus grattardi (Mammalia, Camelidae) from the Shungura Formation, Lower Omo Valley, Ethiopia, and the evolution of African camels. (21st October 2019) - Rowan, John; Martini, Pietro; Likius, Andossa; Merceron, Gildas; Boisserie, Jean-Renaud
Abstract: Camels are exceptionally rare in the Plio-Pleistocene fossil record of Africa, hindering attempts to understand the evolution of this family on the continent. Here we describe recently collected camel specimens from the Shungura Formation, Lower Omo Valley, Ethiopia, and attribute these remains to Camelus grattardi . The new specimens date to the late Pliocene (~3 to 2.6 Ma) and consist of three upper molars, one upper premolar, and two proximal metatarsals. The dental specimens confirm this species' small P4 relative to its molars, a trait that differs significantly from all extant and fossil Old World camels. The metatarsals indicate that C. grattardi was similar in size to the living Bactrian camel, C. bactrianus . Phylogenetically, we find no suitable ancestor, sister, or descendant of the eastern African fossil camel, which suggests greater lineage diversity in Plio-Pleistocene Camelus than previously recognised. Microwear analyses suggest that C. grattardi was likely a mixed-feeder preferring browse, which is consistent with carbon isotopes of enamel from the Turkana Basin. A review of the fossil record of African camels suggests no clear paleoenvironmental association, as fossil camels occur in a range of environments from dry savannas with no permanent water bodies to closed woodlands along the paleo-Omo River.